Legal Certainty Regarding Electronification of Land Certificates (Sertipikat-El) As Proof of Ownership of Land Rights in Indonesia - Diana R. W. Napitupulu (Inovasi Pratama Internasional. Ltd, 2024)
Apart from being a natural resource, land is also an asset or investment material. This urgent land need really requires authentic evidence, namely land certificates, as strong evidence to prevent disputes. As time goes by, manual land certificates will be changed to electronic land certificates. The formulation of the problem in this paper is the legal certainty of electronic land certificates as proof of ownership of land rights in Indonesia. The type of research used is juridical-normative, using a statutory approach ( statute approach ). The results of this research are that an electronic land certificate will be issued if the applicant requests to replace the manual land certificate with an electronic land certificate, and its implementation must continue to be socialized so that more parties know about it and the security of the data in the certificate can be maintained.